Analysis of Indonesian Sharia Banking Performance During the Covid-19 Pandemic (Panzar-Rosse Approach) - Pratama, Nugraha; Albar Tanjung, Ahmad; Sukardi, Sukardi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study was to determine the effect of the Industrial Production Index, Inflation, Third Party Funds, and Measures on the Performance of Islamic Banking in Indonesia and to see the level of competition in Islamic banking during the pandemic. Researchers use a profitability indicator to measure banking performance, namely Return On Assets (ROA). The method in this study uses the scope of this study using a sample of 12 banks registered with the Financial Services Authority (OJK). The data used in this study is monthly data for the period January 2019 to December 2021. In this study, the Auto Regressive Distributed Lag (ARDL) analysis was used. ARDL estimation to obtain short-term and long-term effects. The results showed that the Industrial Production Index variable had a significant negative effect on Return on Assets, the inflation variable had an insignificant effect on Return on Assets, the third-party funds variable had a significant positive effect on Return on Assets, the third-party funds variable had a significant positive effect on Return on Assets, variable third party funds have a significant positive effect on Return on Assets Return on Assets, variable size has a significant positive effect on Return on Assets.